Evidence for a lineage of virulent bacteriophages that target Campylobacter - Cummings Nicola (BMC Genomics, 2010)
Abstract Background Our understanding of the dynamics of genome stability versus gene flux within bacteriophage lineages is limited. Recently, there has been a renewed interest in the use of bacteriophages as 'therapeutic' agents; a prerequisite for their use in such therapies is a thorough understanding of their genetic complement, genome stability and their ecology to avoid the dissemination or mobilisation of phage or bacterial virulence and toxin genes. Campylobacter, a food-borne pathogen, is one of the organisms for which the use of bacteriophage is being considered to reduce human exposure to this organism. Results Sequencing and genome analysis was performed for two Campylobacter bacteriophages. The genomes were extremely similar at the nucleotide level (≥ 96%) with most differences accounted for by novel insertion sequences, DNA methylases and an approximately 10 kb contiguous region of metabolic genes that were dissimilar at the sequence level but similar in gene function between the two phages. Both bacteriophages contained a large number of radical S-adenosylmethionine (SAM) genes, presumably involved in boosting host metabolism during infection, as well as evidence that many genes had been acquired from a wide range of bacterial species. Further bacteriophages, from the UK Campylobacter typing set, were screened for the presence of bacteriophage structural genes, DNA methylases, mobile genetic elements and regulatory genes identified from the genome sequences. The results indicate that many of these bacteriophages are related, with 10 out of 15 showing some relationship to the sequenced genomes. Conclusions Two large virulent Campylobacter bacteriophages were found to show very high levels of sequence conservation despite separation in time and place of isolation. The bacteriophages show adaptations to their host and possess genes that may enhance Campylobacter metabolism, potentially advantaging both the bacteriophage and its host. Genetic conservation has been shown to extend to other Campylobacter bacteriophages, forming a highly conserved lineage of bacteriophages that predate upon campylobacters and indicating that highly adapted bacteriophage genomes can be stable over prolonged periods of time.